2009
DOI: 10.1021/la9031514
|View full text |Cite
|
Sign up to set email alerts
|

Simple, Readily Controllable Palladium Nanoparticle Formation on Surface-Assembled Viral Nanotemplates

Abstract: Transition-metal nanoparticles possess unique size-dependent optical, electronic, and catalytic properties on the nanoscale, which differ significantly from their bulk properties. In particular, palladium (Pd) nanoparticles have properties applicable to a wide range of applications in catalysis and electronics. However, predictable and controllable nanoparticle synthesis remains challenging because of harsh reaction conditions, artifacts from capping agents, and unpredictable growth. Biological supramolecules … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
85
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(87 citation statements)
references
References 54 publications
2
85
0
Order By: Relevance
“…The use of polyelectrolytemodified CPMV was also reported for the templated synthesis of narrowly dispersed Au NPs. Manocchi et al 39,133,134 also reported a size controllable growth of Pd NPs based on surfaced assembled TMV biotemplates and TMV solution by grazing incidence small-angle X-ray scattering (GISAXS). 112 of the virus capsid.…”
Section: Virus-templated Synthesismentioning
confidence: 99%
“…The use of polyelectrolytemodified CPMV was also reported for the templated synthesis of narrowly dispersed Au NPs. Manocchi et al 39,133,134 also reported a size controllable growth of Pd NPs based on surfaced assembled TMV biotemplates and TMV solution by grazing incidence small-angle X-ray scattering (GISAXS). 112 of the virus capsid.…”
Section: Virus-templated Synthesismentioning
confidence: 99%
“…1) The spot was not detected in group C. 2) The protein spot densities analyzed by PDQuest software. the action of enzyme complexes I, II, III, IV, and V, which are located in a special structure of the inner mitochondrial membrane called the mitochondrial respiratory chain 32,33 .…”
Section: Differentially Expressed Apoptosis-related Proteins Identifimentioning
confidence: 99%
“…It provides a modern and innovative approach to develop and test new nanoparticle formulations for electronics, biomedical and therapeutic applications, and various necessities of life 1,2 . Silver nanoparticles (SNPs) represent a prominent nanoproduct with potential applications in medicine and hygiene.…”
Section: Introductionmentioning
confidence: 99%
“…Viral templates (complete viruses or virus-like particles) stand out as bioscaffolds due to their advantageous inner nanometer-range properties: self-assembly capacity, monodispersity, discrete size and shape, stability, symmetry, and biocompatibility [8]. Palladium nanoparticles were synthesized with Tobacco mosaic virus (TMV) as the scaffold in the aqueous phase [9], as part of hydrogel formulations or through hydrothermal reduction [10][11][12][13][14][15], producing complete coverage of the viral particles with a Pd layer or the formation of discrete particles of 1-2 nm, depending on reaction conditions. Additionally, genetically engineered M13 bacteriophages were used as biotemplates for Pd particles obtaining hybrid nanorods and nanowires with potential applications in nanobatteries [16,17].…”
Section: Introductionmentioning
confidence: 99%